2006
DOI: 10.17348/era.4.0.51-60
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Two Quantitative Ethnobotanical Techniques

Abstract: Research AbstractA critical evaluation of two quantitative techniques used in ethnobotanical studies was undertaken using data concerning plant use in a rural community in the semi-arid region of Pernambuco State, northeastern Brazil. The relative importance of 36 native woody species reported as being useful by 98 informants was calculated employing the Use-Value (UV) and Relative Importance (RI) techniques. Both techniques place value on a given taxon based on the number of uses attributed to it. Results obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
162
1
17

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(181 citation statements)
references
References 35 publications
1
162
1
17
Order By: Relevance
“…It is important to point out that the usevalue technique employed in the present study can often over-estimate the value of a species, as has been demonstrated by Albuquerque et al (2006). As such, we limited ourselves here to interpreting it as a measure of utilitarian potential.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is important to point out that the usevalue technique employed in the present study can often over-estimate the value of a species, as has been demonstrated by Albuquerque et al (2006). As such, we limited ourselves here to interpreting it as a measure of utilitarian potential.…”
Section: Discussionmentioning
confidence: 97%
“…A more detailed description of the study area can be found in the works of Albuquerque et al (2006), Albuquerque and Oliveira (2007), Florentino et al (2007), Lucena et al (2007a,b), Monteiro et al (2006a,b), and .…”
Section: Methodsmentioning
confidence: 99%
“…This method has been widely used by several authors to investigate the impact of exploitation on locally important resources, based on the assumption that the more important a resource is, the greater the exploitation pressure will be (e.g. Albuquerque et al 2006, Phillips & Gentry 1993a, Gomez-Beloz 2002, Collins et al 2006. P. butyracea is an evergreen tree which occurs in areas scattered from Guinea, Sierra-Leone, Côte d'Ivoire, Togo, and Benin to the Democratic Republic of Congo, extending eastwards into Tanzania and Uganda where it is being domesticated (Sama & Sacandé 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lucena, comunicação pessoal, 2006). Mais informações sobre a área de trabalho, e diferentes aspectos do uso dos recursos vegetais, podem ser vistas em Albuquerque et al (2006), Lucena et al (2007) e Monteiro et al (2006a,b A fisionomia dos quintais foi descrita por um diagrama de perfil, realizado com base em dois componentes: vertical e horizontal, de acordo com a localização das espécies (Millat-e-Mustafa 1998). A estrutura vertical foi traçada com base nas medidas de DNS e altura das espécies lenhosas da área.…”
unclassified